Model Development for Reduction of Acute Respiratory Tract Infection among Children in Child Care Centers in Songkhla Province - ภูมิบ่อพลับ, บุญชัย; เชี่ยวชาญยนต์, บงกช (Disease Control Journal, 2008)
This study aimed to develop a model to reduce the occurrence of acute respiratory tract infection among pre-school children in child care centers in Songkhla. Participatory Action Research was designed. One thousand and two hundreds pre-school children from 49 care centers were randomly recruited. Data collection was carried out by using the observation checklists. The results revealed that the development of activites and environment in care centers was markly changed with statistical significance (p < 0.01). The satisfaction of teachers was at high level. The morbidity rate of common cold among children was reduced from 46.5% in October 2006 to 25.7% in September 2007. Keys of success were enhanced teacher empowerment and the model with simple activities and recognizable benefits. These factors were important for the sustainability of the center activities. This model were able to reduce incidence rate of ARIC among children in the child care centers so it should be endorsed to be the policy statement of Ministry of Public Health.